Current Trends Regarding the History of the Portuguese Inquisition: What Has Been Done and What Remains - Paiva, José Pedro (2023)
The Portuguese Inquisition, which operated between 1536 and 1821, produced an enormous volume of documents, most of which are archived in the National Archive Torre do Tombo, in Lisbon. The only tribunal of which few information has survived is that of Goa, abolished in 1814 and which saw almost all its trial files burnt that year. Based on the survival sources and regarding the history of the Portuguese Inquisition, what has historiography done already and what remains to be known and deserves more attention? To put it in another way: what do we know and where can or should we go from here?